Being Julia - Szabâo, Istvâan 1938-; Bening, Annette; Irons, Jeremy 1948-; Greenwood, Bruce 1956-; Margolyes, Miriam; Stevenson, Juliet; Koltai, Lajos; Danna, Mychael; Maugham, W. Somerset (William Somerset) 1874-1965 (Sony Pictures Home Entertainment Distributed by Columbia TriStar Home Entertainment, 2005)
Julia is a true diva: beautiful, talented, wealthy and famous. She has a devoted husband who has masterminded her brillant career - but after years of the spotlight she begins to suffer from a severe case of boredom and longs for something new and exciting to put the twinkle back in her eye. She finds what she is looking for in a handsome young American fan, who adds a few more sparks than Julia was hoping for.